Morphometric Evaluation of Bony Nasolacrimal Canal in Mongolians with Primary Acquired Nasolacrimal Duct Obstruction (Central Asian Journal of Medical Sciences, 2022)
Objectives: To compare the morphometric differences of the bony nasolacrimal canal in unilateral primary acquired nasolacrimal duct obstruction (PANDO) patients between PANDO and non-PANDO sides and the control group in the Mongolian population. Methods: A hospital-based, retrospective case-control design was used for this study. A total of 584 participants were grouped into PANDO patients and the control group. Morphometry of the bony nasolacrimal canal was measured by CT scan. Results: The bony nasolacrimal canal’s minimum transverse diameter was 3.67 ± 1.96 mm on the PANDO side, 3.98 ± 2.01 mm on the non - PANDO side and 4.03 ± 1.12 mm for the control group (p > 0.05). The distal bony nasolacrimal canal transverse diameter was 4.39 ± 1.21 mm for the PANDO side, 4.33 ± 1.32 mm on the non-PANDO side and 5.11 ± 1.25 mm for the control groups (p < 0.05). The bony nasolacrimal canal entrance transverse diameter was 4.36 ± 1.59 mm on the PANDO side, 4.43 ± 1.83 mm on the non-PANDO side and 4.69 ± 1.61 mm in the control group (p < 0.05). Conclusion: Narrower bony nasolacrimal canal morphology may cause a tendency for PANDO development. We identified a narrow distal bony nasolacrimal transverse diameter for both the PANDO and non-PANDO sides of unilateral PANDO patients compared with the control group.